Are You Being Served?: Political Accountability and Quality of Government - Alicia Adsera; Carles Boix; Mark Payne (Inter-American Development Bank, Research Department, 2000)
This paper explores, both formally and empirically, the political accountability mechanisms that lie behind the varying levels of public corruption and of effective governance taking place across nations. The first section develops a principal-agent model in which good governance is a function of the extent to which citizens can hold political officials accountable for their actions. Although policy-makers may have strong incentives to appropriate parts of the citizens` income, well-designed institutions (those increasing both informational flows and elite competitiveness) boost political accountability and reduce the space left for the appropriation of rents. The following sections of the paper test the model. The presence of democratic mechanisms of control and an increasingly informed electorate, measured through the frequency of newspaper readership, explain considerably well the distribution of corrupt practices and governmental ineffectiveness in three types of data sets: a large cross-section of countries in the late 1990s for which an extensive battery of governance indicators has been recently developed by Kaufmann et al. (1999a); a panel data set for the period 1980-95 and about 100 nations on corruption and bureaucratic quality based on experts` rankings; and corruption data for the cross-section of US states in the period 1977-95.
Keywords: 330; Korruption; Regierung; Öffentliche Verwaltung; Wirtschaftliche Effizienz; Welt; USA; Governance-Ansatz